2019
DOI: 10.1038/s41598-019-47805-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk to hoary squash bees (Peponapis pruinosa) and other ground-nesting bees from systemic insecticides in agricultural soil

Abstract: Using the hoary squash bee ( Peponapis pruinosa ) as a model, we provide the first probabilistic risk assessment of exposure to systemic insecticides in soil for ground-nesting bees. To assess risk in acute and chronic exposure scenarios in Cucurbita and field crops, concentrations of clothianidin, thiamethoxam and imidacloprid (neonicotinoids) and chlorantraniliprole (anthranilic diamide) in cropped soil were plotted to produce an environmental exposure distributi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 52 publications
0
74
0
Order By: Relevance
“…This species exhibits an unusually high degree of dietary specialization, depending entirely upon Cucurbita crops (Cucurbitaceae) for pollen across most of its range 22,23,25 . Each hoary squash bee female constructs its own nest in the ground 26,27 , commonly within cropping areas 10 where systemic insecticides are often applied as soil drenches or seed treatments 8 .…”
Section: Main Textmentioning
confidence: 99%
See 3 more Smart Citations
“…This species exhibits an unusually high degree of dietary specialization, depending entirely upon Cucurbita crops (Cucurbitaceae) for pollen across most of its range 22,23,25 . Each hoary squash bee female constructs its own nest in the ground 26,27 , commonly within cropping areas 10 where systemic insecticides are often applied as soil drenches or seed treatments 8 .…”
Section: Main Textmentioning
confidence: 99%
“…While all bees that forage on treated crops may be at risk of exposure to systemic pesticide residues in pollen and nectar 28,29 , there is an additional risk of exposure to residues in soil for ground-nesting bees 4,8 . This route of pesticide exposure is currently not considered in regulatory environmental risk assessments for pollinators because honeybees rarely come into direct contact with soil 3,4,7,8 .…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Krupke, et al [97] considered different routes of contamination of beehives with neonicotinoids but focused primarily on the use of coated seeds and granules, which contaminate the soil. Yang, et al [98] found a negative effect of sublethal doses of imidacloprid on honey bee behavior. Feeding individuals with sugar syrup containing 50 µg/L has shown to prolong the time interval between two visits to the feeding site [99,100].…”
Section: Neonicotinoid Insecticidesmentioning
confidence: 99%